Evaluasi Kinerja Angkutan Umum Kota Malang - Bakhtiar, Anang (JU-ke: Jurnal Ketahanan Pangan, 2018)
Transportation is one of the important elements of an urban area. Transportation facilities have potential to control the direction and magnitude of urban development, so that transportation planning has a special position in an urban planning activity. The regional economic growth is always associated with increasing society activities. These society activities will be form a pattern of movements related to society mobility. The level Â movement of the society must be supported by satisfy transportation facilities and infrastructure. This study aims to determine the performance of existing public transport, to know the types of public transportation in accordance with Malang society needs and recommend what kind of type public transportation which is appropriate for Malang City. Based on result study that the performance of the city transportation route AL, ADL and ABG / H and the type of public transportation suits the needs of Malang City based on the criteria of head way and waiting time, Route of city transportation does not match the stipulated waiting time criteria, including ABG / H and ADL. A temporary stop place is known that the city transportation route has a stop place other than the specified terminal. Based on the load factor criteria, it is known that the three AL routes, ADL and ABG / H do not match the criteria for load factors and most vehicles have an average age the vehicle is more than 5 years which can be potentially problematic. Based on peoples perceptions, the type of public transportation that is suitable and can be applied in Malang City is a type of Light Rail Transport (LRT) public transportation. This can be seen from the level of peoples choice of alternative public transportation, namely LRT of 58% and BRT of 42%. Alternative Types of appropriate public transportation are types of Light Rail Transport (LRT) public transportation. This can be seen from the level of peoples choice of alternative public transportation, namely LRT of 58% and BRT of 42%, with the level of each criterion as follows: based on the level of security, 88% LRT and 12% BRT, based on comfort level, LRT of 74% and BRT of 26%, based on the level of timeliness, LRT of 76% and BRT of 24%, based on the rate of compliance, LRT of 57% and BRT of 43%.